The pressure control of independent load port electro-hydraulic load simulation system using fixed time integral sliding mode active disturbance rejection - Hao, He; Yan, Hao (Scientific reports, 2024)
To address the issues of motion disturbance and low loading accuracy in electro-hydraulic load simulation systems, and to effectively mitigate the impact of uncertainty on system performance, this paper proposes a novel independent load port electro-hydraulic load simulation system. A nonlinear variable structure state equation is derived to describe the pressure working states of the left and right chambers of the servo valve and hydraulic cylinder under loading conditions. In light of the presence of substantial motion disturbances, an integrated sliding mode automatic disturbance rejection composite controller is proposed with a focus on fixed-time convergence. To mitigate system chattering and enhance system loading performance and disturbance immunity, a fixed-time integral sliding mode controller was developed within the framework of active disturbance rejection control. Stability analysis was also carried out. Simulation research demonstrates that the pressure control accuracy of the composite controller is 99.88%, 99.86%, and 99.83% respectively when the system step command is given with disturbance frequencies of 1 Hz, 3 Hz, and 5 Hz. Similarly, under the same disturbance frequencies, the pressure control accuracy is 99.88%, 99.86%, and 99.84% respectively when the system sine command is given. The simulation results demonstrate that the independent load port electro-hydraulic load simulation system exhibits a notable energy-saving effect. Specifically, energy savings of around 45% and 48% were achieved compared to the original system. The research and exploration conducted have laid a strong groundwork for future in-depth studies on the independent load port electro-hydraulic load simulation system.